+0  
 
0
46
1
avatar

The expression 3y^2-y-24+10 can be written as (3y + a)(y + b), where a and b are integers. What is a-b?

 May 8, 2022
 #1
avatar+9457 
0

Note that \(3y^2 - y - 24 + 10 = 3y^2 - y - 14\).

 

Then, note that -y = 6y - 7y, so we have:

 

\(\begin{array}{cl} & 3y^2 - y - 14\\ =& 3y^2 + 6y - 7y - 14\\ =& 3y(y + 2) - 7(y + 2) \end{array}\)

 

Now you can take out the common factor (y + 2) and compare with what the question gave you. Can you proceed from here?

 May 8, 2022

11 Online Users

avatar